2017
DOI: 10.3947/ic.2017.49.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines for the Antibiotic Treatment for Community-Acquired Skin and Soft Tissue Infection

Abstract: Skin and soft tissue infection (SSTI) is common and important infectious disease. This work represents an update to 2012 Korean guideline for SSTI. The present guideline was developed by the adaptation method. This clinical guideline provides recommendations for the diagnosis and management of SSTI, including impetigo/ecthyma, purulent skin and soft tissue infection, erysipelas and cellulitis, necrotizing fasciitis, pyomyositis, clostridial myonecrosis, and human/animal bite. This guideline targets community-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
21

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 92 publications
2
52
1
21
Order By: Relevance
“…Macía-Rodríguez et al reported that an inadequate empirical therapy of SSTI resulted in greater mortality (OR 44.74, 95% CI 5.40-370.73) (Macía-Rodríguez et al, 2017). Although the present study data did not show an increase in hospital stay, complications, or mortality for patients with MRSA SSTI, which may be explained by younger age and fewer comorbidities in the MRSA SSTI group and limited power in our sample, it confirms the need for MRSA coverage in purulent SSTI to attempt to improve microbiological cure (Stevens et al, 2014;Kwak et al, 2017). More studies are needed to assess the impact of inappropriate initial therapy on outcomes.…”
Section: Discussioncontrasting
confidence: 58%
“…Macía-Rodríguez et al reported that an inadequate empirical therapy of SSTI resulted in greater mortality (OR 44.74, 95% CI 5.40-370.73) (Macía-Rodríguez et al, 2017). Although the present study data did not show an increase in hospital stay, complications, or mortality for patients with MRSA SSTI, which may be explained by younger age and fewer comorbidities in the MRSA SSTI group and limited power in our sample, it confirms the need for MRSA coverage in purulent SSTI to attempt to improve microbiological cure (Stevens et al, 2014;Kwak et al, 2017). More studies are needed to assess the impact of inappropriate initial therapy on outcomes.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, blood, aspirate and other biopsy material cultures are no longer routinely recommended for simple, nonpurulent CA-SSTIs because of low isolation of causative microorganism rates (12). In another domestic guideline recently reported by the Korean authors, routine blood, aspiration, or punch biopsy culture was recommended only in immunosuppressive patients, similar to that reported in the IDSA guideline (14) In our study, causative microorganisms were isolated from 47% of included patients; in other words, our bacteria isolation rate was higher than that reported previously (12). We attribute this high rate to the facts that patients with CSSTI comprised 57% of our study population and that most cultures were grown from deep swab and tissue samples.…”
Section: Discussionmentioning
confidence: 85%
“…Necrotizing infections most commonly involve the muscular fascial layers but may also involve the dermal, subcutaneous, and muscle layers and warrant prompt, aggressive surgical debridement [4]. Because of the rapid progression of these diseases, most guidelines [3,5,15] recommend broad-spectrum antibiotics to cover GPB and GNB. Our study con rmed the signi cance of antibiotic treatment against GNB.…”
Section: Discussionmentioning
confidence: 99%